Agency Within Tradition: How Muslim Women Become Mediators in Thailand’s Southern Border Provinces - Suthisak Duereh; Tawat Noipom; Aris Hassama (Institut Agama Islam Negeri (IAIN) Pontianak, 2026)
In many Muslim societies, women’s access to religious authority and formal dispute resolution roles remains constrained by patriarchal interpretations of Islamic tradition. This study examines how Muslim women in Thailand’s southern border provinces assume mediation roles and exercise agency within these patriarchal religious structures. Drawing on Saba Mahmood’s conceptualization of agency as inhabitation rather than resistance, the research employs a qualitative design based on in-depth interviews with fifteen mediators and related actors in Pattani, Yala, and Narathiwat. The findings identify three primary pathways into mediation: civil society engagement shaped by experiences of conflict, community-based service grounded in religious and social capital, and formal legal professional development. Across these trajectories, women actively reinterpret the Islamic concept of naṣīḥah (advice) to encompass professional mediation, thereby constructing hybrid forms of religious-professional authority. In practice, mediators integrate fiqh (Islamic jurisprudence), Thai civil law, and local Malay customary norms to resolve domestic violence and inheritance disputes. Despite confronting gender-based stereotypes, security risks in conflict-affected areas, and limited institutional support, they transform these constraints through strategic normative positioning and collective networks. The study argues that legal pluralism can serve as a strategic resource for expanding women’s authority when mobilized through internally grounded religious reinterpretation. By demonstrating how religious authenticity functions as a source of empowerment rather than constraint, this research advances socio-legal scholarship on women’s agency in Islamic contexts and offers policy-relevant insights for strengthening institutional support within plural legal systems. [Di banyak masyarakat Muslim, akses perempuan terhadap otoritas keagamaan dan peran formal dalam penyelesaian sengketa masih dibatasi oleh interpretasi patriarki terhadap tradisi Islam. Studi ini mengkaji bagaimana perempuan Muslim di provinsi perbatasan selatan Thailand memasuki peran mediasi dan menjalankan agensi dalam struktur keagamaan yang patriarki tersebut. Berlandaskan pada konseptualisasi Saba Mahmood mengenai agensi sebagai penghayatan (inhabitation) alih-alih resistensi, penelitian ini menggunakan desain kualitatif melalui wawancara mendalam dengan lima belas mediator dan aktor terkait di Pattani, Yala, dan Narathiwat. Temuan penelitian mengidentifikasi tiga jalur utama menuju peran mediasi: keterlibatan masyarakat sipil yang dibentuk oleh pengalaman konflik, layanan berbasis komunitas yang bertumpu pada modal religius dan sosial, serta pengembangan profesional hukum formal. Di sepanjang jalur tersebut, perempuan secara aktif mereinterpretasi konsep Islam tentang nasihat menjadi praktik mediasi profesional, sehingga membangun bentuk otoritas religius-profesional yang hibrid. Dalam praktiknya, mediator mengintegrasikan fikih Islam, hukum perdata Thailand, dan norma adat Melayu lokal dalam penyelesaian kasus kekerasan dalam rumah tangga dan sengketa waris. Meskipun menghadapi stereotip berbasis gender, risiko keamanan di wilayah konflik, dan keterbatasan dukungan institusional, mereka mentransformasikan kendala tersebut melalui strategi posisi normatif dan jejaring kolektif. Studi ini berargumen bahwa pluralisme hukum dapat berfungsi sebagai sumber strategis bagi perluasan otoritas perempuan ketika dimobilisasi melalui reinterpretasi religius dari dalam. Dengan menunjukkan bahwa autentisitas keagamaan dapat menjadi sumber pemberdayaan alih-alih pembatasan, penelitian ini memperkaya kajian sosio-legal tentang agensi perempuan dalam konteks Islam serta menawarkan implikasi kebijakan bagi penguatan dukungan institusional dalam sistem hukum plural.]